1995
DOI: 10.1097/00005373-199505000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Selective Use of Computed Tomography and Diagnostic Peritoneal Lavage in Blunt Abdominal Trauma

Abstract: The purpose of this study was to attempt to identify those blunt trauma patients in whom expensive diagnostic studies such as computed tomography and diagnostic peritoneal lavage are unnecessary to exclude intra-abdominal injury. The medical records of 1096 blunt trauma patients evaluated at an urban level I trauma center were reviewed. Because of the urgent need to exclude intra-abdominal hemorrhage in patients with hypotension (blood pressure < 90 mm Hg), and the difficulty in obtaining reliable information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 9 publications
0
35
0
3
Order By: Relevance
“…[11,[21][22][23][24] Selective utilization of CT scanning has been advocated for due to radiation exposure and cost. [22][23][24] However, it has been reported that the treatment plan was changed in 6.4% of cases due to diagnoses determined from CT imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,[21][22][23][24] Selective utilization of CT scanning has been advocated for due to radiation exposure and cost. [22][23][24] However, it has been reported that the treatment plan was changed in 6.4% of cases due to diagnoses determined from CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…[11,[21][22][23][24] Selective utilization of CT scanning has been advocated for due to radiation exposure and cost. [22][23][24] However, it has been reported that the treatment plan was changed in 6.4% of cases due to diagnoses determined from CT imaging. [11] It is difficult to conclusively state whether CT scans should be performed selectively or routinely so to better diagnose abdominal solid viscera injury in patients with pelvic bone fractures because of the limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal injuries are characterized by a discrepancy between clinical examination and actual abdominal injuries. In only 26% of all patients with clinical findings suggesting an abdominal injury, the CT showed an abdominal injury [48]. In contrast, pelvic fractures were shown as a risk factor for abdominal injuries [49,50].…”
Section: Abdominal Traumamentioning
confidence: 99%
“…Peritoneal lavaj 2 yaşın altında 250 mİ, 2-5 yaş arasında 500 mİ, 6 yaş ve yu karısında 1000 ml Ringer Laktat infüze edilerek ger çekleştirilir. Peritoneal lavajın pozitiflik kriterleri şun lardır (15,17,19,20):…”
Section: Gereç Ve Yöntemunclassified